Development of Motion Graphic Animation Video Learning Media Assisted by Animakers Based on Problem Based Learning (PBL) in Demak Kingdom Material - Reza Indah Lestari; Kasim Kasim; Meldawati Meldawati (Journal of Pedagogi, 2024)
This research is motivated by the fact that active learning activities are still relatively low and the lack of use of learning media that utilize technology, especially in History subjects. The formulation of the problem in this study is how to design media development and implementation of animated video learning media Motion Graphics assisted by Animaker based on Problem Based Learning (PBL) on the material of the Kingdom of Demak. The purpose of this study is to describe the design of learning media development and implementation of animated video learning media . This research uses the research and development method (Research and Development) with the ADDIE model which consists of 5 (five) stages, namely Analysis , Design , Development , Implementation. and Evaluation . The results of this study indicate that the developed animated video learning media meets the criteria of "very valid" from material experts , media experts , and language experts, obtaining an average value of  90%. Furthermore, the assessment of the educator's practicality test obtained a value of 91% with the category of "Very Practical, whereas, practicality of students obtained a score of 93% with the category of "Very Practical". Based on the assessment of the questionnaire that has been filled out by the validator, educators and students, the animated video learning media Motion Graphics assisted by Animaker based on Problem Based Learning (PBL) that was developed has met the validity and practicality, so it can be concluded that this learning media is very suitable for use in learning.